PKM Produksi dan Pemasaran Hasil Olahan Pepaya di Babadan Polengan Srumbung Magelang - Barbara Gunawan (Jurnal Pengabdian UntukMu NegeRI, 2018)
The target of this PKM program is a group of people who are economically productive (small businesses). The program aims to develop economically independent communities. Business partners in this program are small businesses making and marketing processed papaya products. The problems faced by partners are 1) Product quality that is not so good, 2) Product packaging is still too simple, 3) No product label, 4) No PIRT, 5) No signboard, 6) No promotional media, and 7) Partners do not make financial reports. Outcomes generated from the PKM marketing community service program produced by Papaya in Babadan Polengan Srumbung Magelang are 1) Quality products with elegant packaging, 2) Product label stickers, 3) Products with PIRT, 4) Nameplate, 5) Facebook and Instagram, 6) Financial Statements. The method used to achieve this goal is 1) Training in making papaya sweets, 2) Procurement of plastic packaging and cup sealer tools 3) Making product label stickers, 4) Making PIRT, 5) Making nameplate, 6) Making Facebook and Instagram accounts for partners, 7) Marketing management training, and 8) Training and mentoring in the preparation of financial reports.